Party polarization and citizens' left-right orientations - Freire, A. (Party Politics, 2008)
The article investigates the differences among West European countries in terms of the degree to which individuals' left-right self-placement is anchored in social, value and partisan factors. The study shows that clarity of party alternatives is much more important than political socialization in structuring citizens' left-right attitudes, i.e. the greater the clarity of party alternatives, the more structured the left-right orientations of citizens. As a first step in the investigation, the article seeks to show that the relative weights of social factors in explaining individual left-right self-placement, vis-à-vis values and partisan loyalties, are important, contrary to the poor results of previous studies.